A parametric study on fatigue of a top-tensioned riser subjected to vortex-induced vibrations - Kim, D.K. (Techno Press, 2019)
This study aims to provide useful information on the fatigue assessment of a top-tensioned riser (TTR) subjected to vortex-induced vibration (VIV) by performing parametric study. The effects of principal design parameters, i.e., riser diameter, wall thickness, water depth (related to riser length), top tension, current velocity, and shear rate (or shear profile of current) are investigated. To prepare the base model of TTR for parametric studies, three (3) riser modelling techniques in the OrcaFlex were investigated and validated against a reference model by Knardahl (2012). The selected riser model was used to perform parametric studies to investigate the effects of design parameters on the VIV fatigue damage of TTR. From the obtained comparison results of VIV analysis, it was demonstrated that a model with a single line model ending at the lower flex joint (LFJ) and pinned connection with finite rotation stiffness to simulate the LFJ properties at the bottom end of the line model produced acceptable prediction. Moreover, it was suitable for VIV analysis purposes. Findings from parametric studies showed that VIV fatigue damage increased with increasing current velocity, riser outer diameter and water depth, and decreased with increasing shear rate and top tension of riser. With regard to the effects of wall thickness, it was not significant to VIV fatigue damage of TTR. The detailed outcomes were documented with parametric study results. Â© 2019 Techno-Press, Ltd.